2011
DOI: 10.1111/j.1462-2920.2011.02556.x
|View full text |Cite
|
Sign up to set email alerts
|

New roles for bacterial siderophores in metal transport and tolerance

Abstract: SummarySiderophores are chelators with extremely strong affinity for ferric iron and are best known for their capacity to feed microorganisms with this metal. Despite their preference for iron, they can also chelate numerous other metals with variable affinities. There is also increasing evidence that metals other than iron can activate the production of siderophores by bacteria, thereby implicating siderophores in the homeostasis of metals other than iron and especially heavy metal tolerance. This article con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
310
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 498 publications
(316 citation statements)
references
References 101 publications
4
310
0
2
Order By: Relevance
“…These low-molecular-weight chelators play an important role in enhancing extracellular solubilization of Fe from minerals, making it available to the plant-microbial consortium (Schalk et al, 2011). In addition to Fe, other trace metals, such as Cu, Mn and Zn, are also able to stimulate or inhibit siderophore production.…”
Section: Root Chelation and Compartmentationmentioning
confidence: 99%
“…These low-molecular-weight chelators play an important role in enhancing extracellular solubilization of Fe from minerals, making it available to the plant-microbial consortium (Schalk et al, 2011). In addition to Fe, other trace metals, such as Cu, Mn and Zn, are also able to stimulate or inhibit siderophore production.…”
Section: Root Chelation and Compartmentationmentioning
confidence: 99%
“…Despite their preference for iron, they are also known to chelate a range of other metal ions, e.g., silver, aluminium, cadmium, cobalt, chromium, copper, mercury, manganese, nickel, lead, tin and zinc [63]. There is increasing evidence that these metals can also induce the production of siderophores in bacteria, thereby implying that siderophores might play an important role in heavy metal tolerance by reducing the extracellular concentration of bioavailable metals [63]. In what is the first example of a co-opted metallophore that protects its producer from toxic soluble gold, Johnston et al [62] have shown that upon contact with the gold(III)-complexes D. acidovorans excretes the metallophore delftibactin.…”
Section: Extracellular Compounds For Gold Detoxification-delftia Acidmentioning
confidence: 99%
“…D. acidovorans excretes a secondary metabolite, i.e., a siderophore/metallophore, to alleviate gold(III) toxicity by forming extracellular gold particles [62]. Siderophores/metallophores are chelators with extremely strong affinity for ferric iron and are best known for their capacity to supply this essential nutrient to microorganisms in times of iron limitation [63]. Despite their preference for iron, they are also known to chelate a range of other metal ions, e.g., silver, aluminium, cadmium, cobalt, chromium, copper, mercury, manganese, nickel, lead, tin and zinc [63].…”
Section: Extracellular Compounds For Gold Detoxification-delftia Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…Pyoverdine is a kind of extracellular siderophore of Pseudomonas aeruginosa, which can be largely secreted under iron-deficient conditions [19]. It helps Pseudomonas aeruginosa uptake iron to overcome iron limitation as well as protects them from heavy metal toxicity [20]. As the excellent fluorescence property of pyoverdine, it has already been utilized to established biosensors for the detection of dissociative ferric ion and furazolidone [21,22].…”
Section: Introductionmentioning
confidence: 99%